2014
DOI: 10.3390/en7085273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Impact of Waste Heat Recovery Technologies on Passenger Car Fuel Consumption in a Normalized Driving Cycle

Abstract: Abstract:The purpose of this article was to compare different waste heat recovery system technologies designed for automotive applications. A complete literature review is done and results in two comparative graphs. In the second part, simulation models are built and calibrated in order to assess the fuel consumption reduction that can be achieved on a real driving cycle. The strength of this article is that the models are calibrated using actual data. Finally, those simulations results are analyzed and the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…TEG are based on the Seebeck effect for direct electricity production between two heat sources at different temperatures. Although they have low efficiency and problems due to the increase in the back pressure in the exhaust pipe [11], TEG seems to be the most suitable alternative for energy recovery in light-duty vehicles, where there are space and weight restrictions [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…TEG are based on the Seebeck effect for direct electricity production between two heat sources at different temperatures. Although they have low efficiency and problems due to the increase in the back pressure in the exhaust pipe [11], TEG seems to be the most suitable alternative for energy recovery in light-duty vehicles, where there are space and weight restrictions [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many technologies have been developed for improving the efficiency of engines, such as engine downsizing [2][3][4], the Atkinson or Miller cycle [4][5][6], gasoline direct injection (GDI) [7][8][9], the homogeneous charge compression ignition (HCCI) [10][11][12][13][14], reduction of exhaust energy loss [15,16] or heat loss [17][18][19][20], electrical or precisely controlled cooling systems [20][21][22], and combustion phase control [23]. Cesare et al [1] reported that engine downsizing concepts, such as turbocharging combined with GDI, have contributed to the recent improvements of ICEs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HCCI is an advanced combustion concept for ICEs that has attracted global attention in recent years [10]. Legros et al [16] compared various waste heat treatment technologies, such as Rankine cycles, thermoelectric generators, and turbo compounding, and achieved a fuel reduction of up to 6%. Zhang et al [20] proposed a dynamic control of cooling systems and achieved low heat loss.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the volume ratio on the produced power is also very interesting. An expression has been derived and is given in equation (1). Dividing that expression by the isentropic power gives a ratio of the residual power after a reduction of the volume ratio.…”
Section: Volume Ratiomentioning
confidence: 99%
“…Currently, almost none of them are mature and then are still in research phase. Legros et al [1] have conducted an extensive review of those technologies and provide a comparison between them. The outcome of that comparison shows some advantages of the Rankine cycle heat engine.…”
Section: Introductionmentioning
confidence: 99%